Działania promocyjne przedsiębiorstw na rynku telekomunikacyjnym - Zawadzki, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The hereby article presents promotion as the crucial element of companies' competition in the market of telecommunication services. This instrument is very effectively implemented by operators, which results in extensive profits for them. The author presented forms and strategies of marketing communication, with particular emphasis on strategies based on objectives carried out by means of these forms. The article depicts two most frequently applied forms of promotion i.e. advertising and personal sales, but also other instruments, which influence the level of telecommunication operators targets realization as well as accomplishing competitive advantage. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 230-238